2018
DOI: 10.1021/acs.jpca.8b01836
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Unimolecular Decomposition of JP-8 Jet Fuel Surrogates III: Butylbenzene Isomers (n-, s-, and t-C14H10)

Abstract: Ab initio G3(CCSD,MP2)//B3LYP/6-311G(d,p) calculations of potential energy surfaces have been carried out to unravel the mechanism of the initial stages of pyrolysis of three CH isomers: n-, s-, and t-butylbenzenes. The computed energy and molecular parameters have been utilized in RRKM-master equation calculations to predict temperature- and pressure-dependent rate constants and product branching ratios for the primary unimolecular decomposition of these molecules and for the secondary decomposition of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The use of various compounds in a surrogate fuel mixture is to capture the correct physical and chemical properties and ultimately to model both the physical and chemical processes that occur during combustion in an engine. The aromatic compounds selected for the current work are isomers of butylbenzene, have been found in fuels, and are being investigated for use in surrogates. When comparing different aromatic compounds, 1,3-diethylbenzene offers the widest range of possible speeds of sound, bulk moduli, surface tension, and viscosity. Its properties in mixtures with n -dodecane deviated from ideal mixture behavior the least.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of various compounds in a surrogate fuel mixture is to capture the correct physical and chemical properties and ultimately to model both the physical and chemical processes that occur during combustion in an engine. The aromatic compounds selected for the current work are isomers of butylbenzene, have been found in fuels, and are being investigated for use in surrogates. When comparing different aromatic compounds, 1,3-diethylbenzene offers the widest range of possible speeds of sound, bulk moduli, surface tension, and viscosity. Its properties in mixtures with n -dodecane deviated from ideal mixture behavior the least.…”
Section: Resultsmentioning
confidence: 99%
“…With this approach, the categories of aromatic compounds can be further divided into the number of carbon atoms. These studies have shown the presence of aromatic compounds with 10 carbons. The authors have used n -butylbenzene in the formulation of model mixtures for jet fuel, , and recent studies have begun to examine important reactions involving other butylbenzene isomers. Belisario-Lara and Mebel conducted a computational study to investigate the pyrolysis of n -butylbenzene, sec -butylbenzene, and tert -butylbenzene. Zhang et al performed kinetic studies involving sec -butylbenzene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The number of decomposition products needed to describe subsequent oxidation processes is small as compared to the number of molecules in the original multicomponent fuel. Following this approach, we have recently performed combined experimental and theoretical studies of pyrolysis of a number of important constituents of jet fuels including large alkanes (decane 2 and dodecane 3 ), butylbenzene isomers, 4 and tricyclo[5.2.1.0(2.6)]decane (exo-tetrahydrodicyclopentadiene; exo-TCD; JP-10; C 10 H 16 ). 5,6 These works allowed us to identify the prevailing pyrolysis products for these molecular species and to quantify their relative yields depending on temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, the authors reported on the physical properties of two-component mixtures of iso -butylbenzene, sec -butylbenzene, tert -butylbenzene, or 1,3-diethylbenzene with n -dodecane in the context of surrogate mixtures for various petroleum- or bio-based jet and diesel fuels . The aromatic compounds were chosen for that study because they can represent the 10-carbon aromatic component of fuel in place of n -butylbenzene and they have been the focus of recent fuel studies. The n -dodecane was chosen because it is commonly used to represent the linear alkane category of compounds found in jet fuel. Another category of compounds used in surrogate mixtures is branched alkanes.…”
Section: Introductionmentioning
confidence: 99%